Evaluation of the Implementation of the Government Agency Performance Accountability System (SAKIP) at the Regional Financial Agency - Sandi, Salamah; Muchsin, Slamet; Afifuddin, Afifuddin (Academia Open, 2026)
General Background Public accountability is a fundamental principle of regional government administration because public institutions must report the results of programs, activities, and resource use. Specific Background The Government Agency Performance Accountability System is used to support strategic planning, performance planning, measurement, evaluation, and reporting within the Regional Financial Agency of Pasuruan Regency. Knowledge Gap Although SAKIP supports good governance, its implementation still faces practical limitations, including manual monitoring, weak integration, limited attention to performance outcomes, and insufficient socialization. Aims This study aims to understand the problems, supporting factors, and inhibiting factors in the implementation of SAKIP at the Regional Financial Agency of Pasuruan Regency. Results Using a qualitative descriptive approach and the Miles, Huberman, and Saldana interactive analysis model, the findings show that the formation of the SAKIP team decree supports implementation within the agency. However, monitoring and evaluation need to be conducted every three months and maximized manually. Officers and staff are expected to support SAKIP even when it does not affect additional income. Regular socialization is also needed to strengthen implementation. Novelty This study highlights internal administrative support and behavioral commitment as key aspects of SAKIP implementation. Implications Stronger monitoring, staff commitment, and regular socialization can improve performance accountability and public governance quality. Highlights: Quarterly monitoring was recommended for better evaluation. Staff support remained necessary beyond income incentives. Regular socialization was needed across the agency. Keywords: Policy Implementation, Financial Governance, Good Governance